„Klatka Ezry”. Między poezją a polityką - Sikorski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Ezra Pound 1885–1975 was, next to Thomas Stearns Eliot, the most prominent American poet of modernist. He was considered the creator of vorticism and imagism — modern trends in art and world culture. In his works he reached to different eras and cultural trends. He was as well fascinated by medieval Provençal, Spanish and Italian literature, and Japanese art of haiku. On his work also had an impact scholasticism, Confucianism and Far East literature. In addition to poetry, Pound was also involved in literary criticism, painting and sculpture, he wrote historiosophical essays and dramas. The greatest fame brought him, however, written for many years, „Canto”. During his stay in the British Isles he also dealt with politics and economics. He was considered a supporter of the theory of Social Credit of Hugh Douglas Clifford, aBritish engineer and economic theorist. In the early twenties Pound went to Italy. Here he became fascinated with fascism and the person of Benitto Musollini. In his works including his poetic works appeared clear fascist and anti-Semitic accents. He criticized Jewish international financiers and banking critique of usury. During World War II he gave propaganda „talks” in the Italian radio. He praised the organization of the fascist state and fascism as an idea, and at the same time warned the threat from international Jewish conspiracy. His views meant that he was accused of collaboration and treason. He was arrested and imprisoned in the US prison camp near Genoa. He spent almost amonth in aclosed cage. During his stay in the camp he had nervous breakdown. After transportation to the United States for many years he was locked out in hospital for mentally ill. After leaving the hospital, he returned to public space. Still creative, he was nominated for the most prestigious literary awards. His works have been translated into many languages around the world, including Polish. He died in Italy in 1975.
Keywords: faszyzm; antysemityzm; ideologia i literatura; kultura; ekonomia